Algumas consequências da Supergravidade - Costa, Ranieri Batista da (2015)
Supersymmetry is a very useful tool for extending the Standard Model up to the grand unification scale, studying electoweak symmetry breaking and providing dark matter candidates. The presence of superpartners solves the problem of divergences, and changes the renormalization group equations in a way that allows gauge coupling unification. In a global supersymmetry the breaking scale is proportional to the vacuum energy, which makes it incompatible with the low value of the cosmological constant. Promoting SUSY to a local symmetry results in supergravity, which mandates existence of a spin-2 gravitational field, naturally integrates General Relativity and particle physics, and is required to adjust the potential and obtain a high breaking scale with low cosmological constant. This review work looks into models based on gravity-mediated supersymmetry breaking. These models allow a simpler hidden sector than their gauge-mediated or anomay-mediated counterparts. And the lightest supersymmetric particles, higgsino-like, could be detected once an electron-positron collider such as ILC is ready.